ANALYSIS TYPES AND FUNCTIONS OF TABOO WORDS IN “THE WOLF OF WALL STREET” MOVIE - Dewi Putri Rahmayani; Fitrawati Fitrawati (Universitas Negeri Padang, 2018)
In linguistics, everyone has his own way of expressing his feelings. One such way is by using taboo language. Taboo language not only happens in everyday life, but also in a movie. This study aims to find the types of taboo language as well as the functions contained in every utterance used by the characters in the western film entitled